Proposta de um protocolo de terapia celular para o tratamento da doença pulmonar obstrutiva crônica - Ribeiro-Paes, J. T. [UNESP]; Stessuk, T.; Marcelino, M.; Faria, C.; Marinelli, T.; Ribeiro-Paes, M. J. (Elsevier B.V., 2014)
The main feature of pulmonary emphysema is airflow obstruction resulting from the destruction of the alveolar walls distal to the terminal bronchioles. Existing clinical approaches have improved and extended the quality of life of emphysema patients. However, no treatment currently exists that can change the disease course and cure the patient. The different therapeutic approaches that are available aim to increase survival and/or enhance the quality of life of emphysema patients. In this context, cell therapy is a promising therapeutic approach with great potential for degenerative pulmonary diseases. In this protocol proposition, all patients will be submitted to laboratory tests, such as evaluation of heart and lung function and routine examinations. Stem cells will be harvested by means of 10 punctures on each anterior iliac crest, collecting a total volume of 200 mL bone marrow. After preparation, separation, counting and labeling (optional) of the mononuclear cells, the patients will receive an intravenous infusion from the pool of Bone Marrow Mononuclear Cells (BMMC). This article proposes a rational and safe clinical cellular therapy protocol which has the potential for developing new projects and can serve as a methodological reference for formulating clinical application protocols related to the use of cellular therapy in COPD. This study protocol was submitted and approved by the Brazilian National Committee of Ethics in Research (CONEP - Brazil) registration number 14764. It is also registered in ClinicalTrials.gov (NCT01110252). (c) 2013 Sociedade Portuguesa de Pneumologia. Published by Elsevier Espana, S.L. All rights reserved.
A protocol proposition of cell therapy for the treatment of chronic obstructive pulmonary disease
Keywords: Cell therapy; Chronic obstructive pulmonary disease; Pulmonary emphysema; Stern cells